Pelatihan dan Pendampingan Pembuatan Media Pembelajaran Menggunakan Powtoon Untuk Guru SMP di Batam - Devega, Army Trilidia; Herasmus , Hilda; Irfan, Muhammad (PUAN INDONESIA, 2024)
The Training and Mentoring Program for Creating Learning Media Using Powtoon for Junior High School Teachers in Batam is an important initiative to enhance teachers' competence in utilizing modern technology in the teaching and learning process. In this digital era, interactive and engaging learning media are essential to foster students' interest in learning. Through this program, junior high school teachers in Batam received intensive training on the use of Powtoon, a platform that allows the creation of interesting and easy-to-use animated videos. In addition to training, mentoring was also provided to ensure that teachers could produce effective learning media that align with their teaching materials. This program not only focuses on improving teachers' technical skills but also encourages creativity and innovation in presenting learning materials. With full support from the mentoring team, teachers can create engaging and interactive learning videos, which are expected to enhance student engagement and learning outcomes. The results of this training show that teachers in Batam are now more confident in using technology as a teaching aid, which will ultimately have a positive impact on the quality of education in the city.